Long-term ozone changes and associated climate impacts in CMIP5 simulations - Eyring, Veronika; Arblaster, J. M.; Cionni, I.; Sedlacek, J.; Perlwitz, J.; Young, P.J.; Bekki, S.; Bergmann, D.; Cameron-Smith, P.; Collins, W.J.; Faluvegi, G.; Gottschaldt, Klaus-Dirk; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Ozone changes and associated climate impacts in the Coupled Model Intercomparison Project Phase 5 (CMIP5) simulations are analyzed over the historical (1960–2005) and future (2006–2100) period under four Representative Concentration Pathways (RCP). In contrast to CMIP3, where half of the models prescribed constant stratospheric ozone, CMIP5 models all consider past ozone depletion and future ozone recovery. Multimodel mean climatologies and long-term changes in total and tropospheric column ozone calculated from CMIP5 models with either interactive or prescribed ozone are in reasonable agreement with observations. However, some large deviations from observations exist for individual models with interactive chemistry, and these models are excluded in the projections. Stratospheric ozone projections forced with a single halogen, but four greenhouse gas (GHG) scenarios show largest differences in the northern midlatitudes and in the Arctic in spring (~20 and 40 Dobson units (DU) by 2100, respectively).